Museum Studies Borderlands: Negotiating Curriculum and Competencies (Cadernos de Sociomuseologia, 2012)
Given ICTOP‘s work on revising the curriculum guide using the competencies approach (2000-2008), the author asks whether it is possible to reflect some of the issues and conceptual underpinnings that are at play in the discourse of museology/museum studies as a field of study and pedagogy when designing curriculum when taking the competencies approach. Until we address this question, ICTOP‘s work will have little relevance for the design of syllabi/curriculum by post-secondary institutions. This presentation lays out some of the professional issues underlying and the role for critical reflexive professionalism which can bridge theory and practice, competencies and epistemological knowledge and s how a way forward. Then it moves to address some of the territories where critical discussion is at work that would extend the curriculum discussions of ICTOP, while pointing to some developments that offer a museology of possibilities.